PENGUKURAN CUSTOMER LOYALTY MELALUI ANALISIS EXPERIENTIAL MARKETING, SERVICE QUALITY DAN BRAND IMAGE DENGAN CUSTOMER VALUE SEBAGAI VARIABLE INTERVENING - Natalia, Natalia; Putra, Andriansyah Sumanto; Melati, Ina (Journal of Business Strategy and Execution, 2014)
This observation is done to find out how much the experiential marketing, service quality and brand image has influenced the customer value and the effect to the customer loyalty of Kereta Api Argo Bromo Anggrek relation Jakarta-Surabaya. The problem that Kereta Api Argo Bromo is facing is that there is a decreasing of passenger’s volume since the last 5 years and the low income compared to the other executive train in the previous period. Analysis of studies using path analysis where the data was obtained through deployment to 145 customers Argo Bromo Anggrek Train relationships Jakarta - Surabaya with random sampling techniques of probability sampling. The results achieved are experiential marketing, service quality and brand image has a significant effect simultaneously to customer value. experiential marketing, service quality, brand image and customer value has a significant effect on customer loyalty. Partially, service quality does not have a significant effect on customer loyalty.